Bahasa English - Fauzan Fauzan; Sulistyo Sulistyo; Rita Indah Mustikowati; Sri Wilujeng (Jurnal Manajemen Indonesia, 2023)
Entrepreneurship education is a field that develops and occupies an important position in the policy agenda in many countries. The research objective is to identify the research trend of entrepreneurship education as well as the scientific production from time to time, such as: sources, authors, and documents. The bibliometric analysis was used to analize the sample from 2176 articles which have been published between 1977 to 2021. To get the metadata from the Scopus bibliography database, on Friday, 23rd of July 2021, at 2:56 pm, it used the “entrepreneurship AND education” query in the article title. Microsoft Excel was used to do the frequency analysis, VOSviewer was used to visualize the data, and Harzing's Publish or Perish was used as citation metrics. The result showed the improvement in the literature about entrepreneurship education from 1980 until 2021, and the improvement happened in 2010. There is many research about entrepreneurship education which involves multi-author collaboration, those are published in multi-language, with total of 160 authors from 109 different countries and 160 institutions. The United States is the biggest contributor to this research, followed by China, The United Kingdom, Spain, and Indonesia. The most publication about entrepreneurship education published by Education and Training. This finding can help further research related to the overview of entrepreneurship education worldwide from time to time. This paper also proposes several future avenues of entrepreneurship education research. In future research, it is recommended to expand the use of the database and includes more fields in the search.